RISE: High energy material research laboratory (HEMREL) / Dr Shahril Anuar Bahari - Anuar Bahari, Shahril (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
High Energy Material Research Laboratory, (UiTM - MTC HEMREL) was established in University Teknologi MARA under the Micro Industry Hub (MIH) program together with MTC Engineering Sdn Bhd.